Sistem Informasi E-Marketplace Penyewaan Dekorasi Berbasis Web - Uchti Nur Rachmah; Irfan Mahendra (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2022)
ABSTRACT Uchti Nur Rachmah (11200418), Web-Based Decoration Rental E-Marketplace Information System. Decoration is an important part as a living atmosphere in the organization of an event organized by individuals or organizations. As a visual element, decorations for various types of events such as weddings, engagements, birthday celebrations, to celebrations on big days are largely determined by the suitability of the theme of the event itself. The obstacle that is often encountered by decoration tenants today is the lack of information obtained about decoration rental providers, making it difficult to determine the choice of decoration according to the desired criteria. In addition, tenants who come directly to ask for decorations need to take time which reduces the effectiveness of the decoration selection process. Moreover, if the tenant intends to compare prices from one rental provider to another. The software development method used by the author in this study is the agile method. The agile approach allows developers to be ready to make changes by iterating over the software development stage. Through the Web-Based Decoration Rental E-Marketplace Information System, the author provides a solution to help decoration tenants to more easily get price information from various rental providers as well as to make decoration rental transactions. Keywords: Information System, Decoration, Rental, E-Marketplace.